2001
DOI: 10.1046/j.0022-202x.2001.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

The p38-MAPK/SAPK Pathway is Required for Human Keratinocyte Migration on Dermal Collagen

Abstract: Human keratinocyte motility plays an important role in the re-epithelialization of human skin wounds. The wound bed over which human keratinocytes migrate is rich in extracellular matrices, such as fibrin, fibronectin, and collagen, and serum factors, such as platelet-derived growth factor and transforming growth factor beta 1. Extracellular matrices and the serum factors bind to cell surface receptors and initiate a cascade of intracellular signaling events that regulate cell migration. In this study, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
52
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 58 publications
8
52
0
Order By: Relevance
“…p38MAPK has also been shown to be required for TGF-b-dependent stimulation of matrix production in dermal fibroblasts, and thus inhibition of p38MAPK could potentially be effective in preventing dermal scarring. 24,26,30 It has also been shown that p38MAPK-dependent activation of Smad3 promoted deposition of extracellular matrix by myofibroblasts both in vitro and in vivo. 24,26,30,31 These reports together with our findings lead us to hypothesize that inhibition of p38MAPK may be beneficial in preventing/treating PVR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…p38MAPK has also been shown to be required for TGF-b-dependent stimulation of matrix production in dermal fibroblasts, and thus inhibition of p38MAPK could potentially be effective in preventing dermal scarring. 24,26,30 It has also been shown that p38MAPK-dependent activation of Smad3 promoted deposition of extracellular matrix by myofibroblasts both in vitro and in vivo. 24,26,30,31 These reports together with our findings lead us to hypothesize that inhibition of p38MAPK may be beneficial in preventing/treating PVR.…”
Section: Discussionmentioning
confidence: 99%
“…24,26,30 It has also been shown that p38MAPK-dependent activation of Smad3 promoted deposition of extracellular matrix by myofibroblasts both in vitro and in vivo. 24,26,30,31 These reports together with our findings lead us to hypothesize that inhibition of p38MAPK may be beneficial in preventing/treating PVR. Although PVR is caused by the activation of many cell types, that is, retinal glial components, vascular cells, and so on, activation and fibroblastic transformation of RPE cells is a critical feature in the development of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of p38 MAPKs are mediated by various p38 MAPK substrates including MAPK-activated protein kinase 2 (MK2), MK3, and p38 MAPK-activated kinase (PRAK) (9,10). In addition to the more defined role in inflammation and cell stress responses (11), p38 MAPK has also been implicated in the cytoskeleton reorganization and the cellular migration of various cell types (12)(13)(14)(15)(16)(17)(18). The use of specific inhibitors has demonstrated the importance of p38 MAPK in endothelial cell migration stimulated by angiogenic factors such as VEGF (19).…”
mentioning
confidence: 99%